5s-3=17+9s

Simple and best practice solution for 5s-3=17+9s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5s-3=17+9s equation:


Simplifying
5s + -3 = 17 + 9s

Reorder the terms:
-3 + 5s = 17 + 9s

Solving
-3 + 5s = 17 + 9s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-9s' to each side of the equation.
-3 + 5s + -9s = 17 + 9s + -9s

Combine like terms: 5s + -9s = -4s
-3 + -4s = 17 + 9s + -9s

Combine like terms: 9s + -9s = 0
-3 + -4s = 17 + 0
-3 + -4s = 17

Add '3' to each side of the equation.
-3 + 3 + -4s = 17 + 3

Combine like terms: -3 + 3 = 0
0 + -4s = 17 + 3
-4s = 17 + 3

Combine like terms: 17 + 3 = 20
-4s = 20

Divide each side by '-4'.
s = -5

Simplifying
s = -5

See similar equations:

| x-0.7=9.82 | | -17m=34 | | (4-3x)(4+3x)= | | 1t=0.2s+10 | | (x^4)+(10x^2)+49= | | 13x-(4x-9)=63 | | (16y+1)-(5y-7)=4y-5 | | 13x+29y=-3 | | 25n=450 | | 4(3q-4)= | | log(x^2+6x+960)=3 | | -8n+1=-6-5 | | T=0.2s+10 | | 4y+8x=120 | | 104=x+(x+5)+5x-6 | | d-(12)=-73 | | 3*x-11=x+33 | | d-(12)=-733 | | 3x+45+7x+5=90 | | h-4=kforj | | -5(3x+2)-x=22 | | -3(x+9)=30 | | 3*x-11=x+34 | | 48x^2-50x+7=0 | | 9x^2-4x+1=0 | | 6x^3-9x^2-2x+3=0 | | 8-9(-4x+7)= | | 46-5=-6y | | 3x+45+7x+5=180 | | 9x+4=8x+6 | | .99=10+.89d | | (18-3x)-(4+2x)=10 |

Equations solver categories